PENGARUH MEDIA VIDEO ANIMASI TERHADAP MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Meizahwa, Elsya; Erlisnawati; Zufriady (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the significant effect of the use of animated video media on students’ learning interest in the IPAS subject for fourth-grade elementary school students. This study employed a quantitative approach with a Pre-Experimental research design using the one group pretest-posttest design. The population of this study consisted of all fourth-grade students of SD MIT Fathrizk Pekanbaru. The sample of this study was class IVA students totaling 25 students selected using a purposive sampling technique. Data collection techniques used in this study were questionnaires, observation, interviews, and documentation. The data analysis techniques included descriptive statistical analysis, normality test, homogeneity test, and hypothesis testing using the paired sample t-test (t-test). The results of the study indicate that there was an increase in students’ learning interest after the use of animated video media in the learning process. Based on the descriptive statistical analysis, the average score of students’ learning interest increased from 10.88 in the pretest to 17.50 in the posttest after the implementation of animated video media in the learning process. The increase in the average score was 6.62 or approximately 60.84%. The results of the normality test showed that the pretest and posttest data were normally distributed, while the homogeneity test indicated that the data were homogeneous. After fulfilling these prerequisite tests, hypothesis testing was conducted using the paired sample t-test. The results of the hypothesis test showed that the significance value (Sig. 2-tailed) was < 0.001, indicating that Ha was accepted and H₀ was rejected.